SB203580, a pharmacological inhibitor of p38 MAP kinase transduction pathway activates ERK and JNK MAP kinases in primary cultures of human hepatocytes - Henklová, Pavla; Vrzal, Radim; Papoušková, Barbora; Bednář, Petr; Jančová, Petra; Anzenbacherová, Eva; Ulrichová, Jitka; Maurel, Patrick; Pávek, Petr; Dvořák, Zdeněk (European journal of pharmacology, 2008)
Mitogen-activated protein kinases (MAPKs) were extensively studied in cancer-derived cell lines; however, studies in non-transformed human cells are scarce. In the current paper, we studied the effect of SB203580, a pharmacological inhibitor of p38 MAPK, on activation and inhibition of p38 MAPK transduction partway in primary human hepatocytes (in vitro model of differentiated cells) in comparison with several tumor cell lines (proliferating non-differentiated in vitro model). In addition, we analyzed the effect of SB203580 on extracellular-regulated protein kinase (ERK) and c-jun-N-terminal kinase (JNK) pathways both in primary human hepatocytes and tumor cell lines employing primary antibodies detecting phosphorylated kinases. We show that SB203580 activates ERK and JNK in primary cultures of human hepatocytes. The levels of ERK-P(Thr202/Tyr204), JNK-P(Thr183/Tyr185) and c-Jun-P(Ser63/73), a target down-stream protein of JNK, were increased by SB203580. In contrast, SB203580 activated ERK but not JNK in HepG2, HL-60, Saos-2 and HaCaT human cancer cell lines. We tested, whether the effects of SB203580 are due to metabolism. Using liquid chromatography/mass spectrometry, we found one minor metabolite in human liver microsomes but not in HepG2 cells. These data imply that biotransformation could be responsible for the effects of SB203580 in human hepatocytes. This study is the first report on the effects of MAPK activators (sorbitol, anisomycin, EGF) and MAPK inhibitors in primary human hepatocytes. We observed differential effects of these compounds in primary human hepatocytes and in cancer cells, implying the cell-type specificity and the essential differences between the role and function of MAPKs in normal and cancer cells.
Keywords: hepatocyty; financování organizované; aktivace enzymů; p38 Mitogen-Activated Protein Kinases; pyridiny; vztah mezi dávkou a účinkem léčiva; HL-60 buňky; interakce mezi receptory a ligandy; buněčné linie; JNK Mitogen-Activated Protein Kinases; Blotting, Western; Enzyme Activation; Receptor Cross-Talk; Enzyme Inhibitors; lidé; signální transdukce; HL-60 Cells; kultivované buňky; Signal Transduction; jaterní mikrozomy; mitogenem aktivované proteinkinasy p38; Hepatocytes; Cell Line; JNK mitogenem aktivované proteinkinasy; Humans; hmotnostní spektrometrie s elektrosprejovou ionizací; western blotting; Cells, Cultured; Imidazoles; Financing, Organized; Dose-Response Relationship, Drug; inhibitory enzymů; Pyridines; Microsomes, Liver; Cell Survival; viabilita buněk; Spectrometry, Mass, Electrospray Ionization; extracelulárním signálem regulované MAP kinasy; imidazoly; Extracellular Signal-Regulated MAP Kinases